An investigation on the effect of investor’s behavior on fund management - Abolfazl Danaei; Younos Vakil Alroaia; Majid Razinia (Management Science Letters)
There are many evidences to believe that investors’ personal characteristics influence on their financial decisions when they purchase stocks, bounds, etc. In this paper, we present an empirical investigation to study the effects of 20 personal characteristics on 52 managers of mutual funds in Iran. Using Pearson correlation test, the study has detected that seven factors including anchoring & adjustment, framing, over confidence, illusion of control, hindsight, recency and self-attribution positively influence on investors’ behaviors. In addition, five factors including consistency, self-control, loss aversion, regret aversion and availability negatively influence on investors’ behaviors. However, the study did not find any evidence to confirm any kind of relationship of representativeness, conservatism, ambiguity aversion, optimism, mental accounting, confirmation and status quo on investors’ behaviors.